2020
DOI: 10.1371/journal.pone.0230438
|View full text |Cite
|
Sign up to set email alerts
|

Investigating discharge communication for chronic disease patients in three hospitals in India

Abstract: Poor discharge communication is associated with negative health outcomes in high-income countries. However, quality of discharge communication has received little attention in India and many other low and middle-income countries. Primary objective To investigate verbal and documented discharge communication for chronic non-communicable disease (NCD) patients. Secondary objective To explore the relationship between quality of discharge communication and health outcomes. Methods Design Prospective study. Setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…The information is combined both verbal and non-verbal methods of education information, for instance banners, pamphlets and inquiring to consultation with healthcare provider via LINE group. 17 This approach has also been established by few other studies, 18 21 which shows that the literacy is further increased because of the patient has an opportunity to interact with the respective diseases and get educated. 22 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The information is combined both verbal and non-verbal methods of education information, for instance banners, pamphlets and inquiring to consultation with healthcare provider via LINE group. 17 This approach has also been established by few other studies, 18 21 which shows that the literacy is further increased because of the patient has an opportunity to interact with the respective diseases and get educated. 22 …”
Section: Discussionmentioning
confidence: 93%
“…The information is combined both verbal and non-verbal methods of education information, for instance banners, pamphlets and inquiring to consultation with healthcare provider via LINE group. 17 This approach has also been established by few other studies, [18][19][20][21] which shows that the literacy is further increased because of the patient has an opportunity to interact with the respective diseases and get educated. 22 This study also showed that diet behavior among T2DM patients played a highly significant role in blood sugar levels control with increased odds ratio in the model of multivariate analysis (AOR=9.71; 95%CI=5.98-15.77; p-value<0.001).…”
Section: Discussionmentioning
confidence: 94%
“…Given the importance placed on communication as a human resource factor in every organizational setting and an integral part of interpersonal relations, the current study finds the theory in a better position to explain the discharge communication practices (from the orientation, identification, exploitation and through to the resolution phase) that influence the patient health outcomes of in surgical wards at the Kenyatta National Hospital. Humphries et al (2020) explored the relationship between quality of discharge communication and health outcomes. The studies concentrated on 546 chronic NCD (chronic respiratory disease, cardiovascular disease or diabetes) patients.…”
Section: Peplau's Interpersonal Relations Theorymentioning
confidence: 99%
“…Poor communication between healthcare professionals and patients and/or relatives is abundant (Vermeir et al, 2015;Akinyelure et al, 2022) and can lead to decreased medication adherence (Kvarnström et al, 2021) and adverse health outcomes (Giardina et al, 2020;Humphries et al, 2020). A study has shown that physicians' attention to contextual factors with importance for the patients often was compromised, leading to less individualised patient care (Weiner et al, 2010).…”
Section: Introductionmentioning
confidence: 99%